2021
DOI: 10.3390/ma14112830
|View full text |Cite
|
Sign up to set email alerts
|

Highly Water Dispersible Functionalized Graphene by Thermal Thiol-Ene Click Chemistry

Abstract: Functionalization of pristine graphene to achieve high water dispersibility remains as a key obstacle owing to the high hydrophobicity and absence of reactive functional groups on the graphene surface. Herein, a green and simple modification approach to prepare highly dispersible functionalized graphene via thermal thiol-ene click reaction was successfully demonstrated on pristine graphene. Specific chemical functionalities (–COO, –NH2 and –S) on the thiol precursor (L-cysteine ethyl ester) were clicked direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The increase in the ID/IG band ratio reveals the covale tionalization, and the ID/IG spatial map indicates the functionalization prefers to o the edges. A thiol-ene click reaction between L-cysteine ethyl ester and graphene was deployed by Dusan's group to introduce amino groups to pristine graphene (Scheme 5) [19]. The functionalized graphene shows a significant increase in the S2p, N1s, and O1s peaks at 164.0 eV, 401.5 eV, and 531.0 eV in the XPS spectra, indicating the presence of L-cysteine ethyl ester.…”
Section: Carboxylic Acid Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the ID/IG band ratio reveals the covale tionalization, and the ID/IG spatial map indicates the functionalization prefers to o the edges. A thiol-ene click reaction between L-cysteine ethyl ester and graphene was deployed by Dusan's group to introduce amino groups to pristine graphene (Scheme 5) [19]. The functionalized graphene shows a significant increase in the S2p, N1s, and O1s peaks at 164.0 eV, 401.5 eV, and 531.0 eV in the XPS spectra, indicating the presence of L-cysteine ethyl ester.…”
Section: Carboxylic Acid Groupmentioning
confidence: 99%
“…The thiol-ene click reaction between L-cysteine ethyl ester and graphene. Reproduced with permission from [19], copyright 2021 Multidisciplinary Digital Publishing Institute.…”
Section: Carboxylic Acid Groupmentioning
confidence: 99%
“…One is the covalent functionalization of graphene by grafting functional groups such as hydroxyl, 10,11 carboxyls, 12,13 or amino groups. 14,15 The other employs non-covalently functionalized graphene flakes to achieve stable dispersion in polar media using specific metal particles, 16 organic molecules, 17,18 polymers, 19−21 and biomolecules 22,23 as stabilizers. One feasible method is to disperse graphene directly in the solvent during the production process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, it is difficult for graphene to be employed in many fields because of its high hydrophobicity and is easily aggregated in solution due to the mismatch of graphene surface tension and the strong π–π interaction between sp 2 -conjugated structures. , To date, two ways have been adopted to increase graphene hydrophilicity. One is the covalent functionalization of graphene by grafting functional groups such as hydroxyl, , carboxyls, , or amino groups. , The other employs non-covalently functionalized graphene flakes to achieve stable dispersion in polar media using specific metal particles, organic molecules, , polymers, and biomolecules , as stabilizers. One feasible method is to disperse graphene directly in the solvent during the production process. , For example, highly stable reduced graphene oxide (rGO) dispersion was produced by the reducing graphene oxide (GO) method. , In addition, pyrene derivatives , and ionic liquids , can serve as effective stabilizers for graphene in liquid-phase exfoliation and have the potential to achieve high concentrations of graphene in solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The theme of graphene functionalization/dispersion is still very active, particularly for environmentally friendly and effective methods that do not require the use of strong acids or oxidants. Farivar et al [ 16 ] reported a simple and green modification method for preparing highly dispersible functionalized graphene via thermal thiol-ene click reactions. The method provides specific chemical functionalities such as –COO, –NH 2 and –S to the graphene sheets by using modified L-cysteine ethyl ester.…”
mentioning
confidence: 99%